2021
DOI: 10.3390/ijerph182413230
|View full text |Cite
|
Sign up to set email alerts
|

Redefinition and Measurement Dimensions of Sustainable Employability Based on the swAge-Model

Abstract: Objectives: To solve the labour shortage, we clarify the definition and dimensions of sustainable employability, and make it possible to develop sustainable employability scales in the future and lay the foundation for subsequent quantitative research. Finally, people’s sustainable employability can be improved. Highly sustainable employability employees can continue to work in the labour market and their working lives can be prolonged. Labour market supply will increase and labour shortage will be partly solv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…For example, building on the Ability-Motivation-Opportunity framework, Le Blanc et al [ 5 ] addressed the topic as the “extent to which a worker is able, willing, and has opportunities to work now and in the future” (p.3). Centering on work value and macro factors, Deng et al [ 6 ] defined SE as “the ability of individuals, who pursue work with high intrinsic value and avoid digital exclusion, to remain in employment during their lifetimes” (p. 6). Recently, using proximal constructs, Fleuren et al [ 7 ] defined SE as an “individual’s ability to function at work and in the labor market, or their ‘employability’, which is not negatively, and preferably positively, affected by that individual’s employment over time” (p. 15) and proposed nine indicators reflecting health, well-being, and employability components to measure SE over time.…”
Section: Introductionmentioning
confidence: 99%
“…For example, building on the Ability-Motivation-Opportunity framework, Le Blanc et al [ 5 ] addressed the topic as the “extent to which a worker is able, willing, and has opportunities to work now and in the future” (p.3). Centering on work value and macro factors, Deng et al [ 6 ] defined SE as “the ability of individuals, who pursue work with high intrinsic value and avoid digital exclusion, to remain in employment during their lifetimes” (p. 6). Recently, using proximal constructs, Fleuren et al [ 7 ] defined SE as an “individual’s ability to function at work and in the labor market, or their ‘employability’, which is not negatively, and preferably positively, affected by that individual’s employment over time” (p. 15) and proposed nine indicators reflecting health, well-being, and employability components to measure SE over time.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that no consensus exists for a "sustainable working life," meriting further studies. The paper by Deng et al [20] proposes the development of new ways of measuring sustainable employability. This paper argues for the SwAge-model.…”
Section: Conclusion Of the New Knowledgementioning
confidence: 99%
“…In essence, the CA starts from different conceptual and scientific principles [2], in comparison to positivistic research methods often used in the field of SE [12][13][14]. Central to the CA are normativity, diversity and contextuality.…”
Section: Sustainable Employabilitymentioning
confidence: 99%
“…In the Job Demand-Resource model [8], recent developments have indirectly included personal values of the employee in studies by focussing on the person-job fit and job crafting [3,[9][10][11]. Other scholars have developed new conceptualizations and value based operationalizations of sustainable employability [12][13][14].…”
Section: Introductionmentioning
confidence: 99%